REFLEKSJA W ZAWODZIE NAUCZYCIELA – ZAŁOŻENIA A REALNE MOŻLIWOŚCI REALIZACJI - Zawadzka-Bartnik, Elżbieta (Neofilolog, 2019)
The category of reflection has a long tradition in education. The aim of this article is to focus on the reasons for the difficulties of putting this construct into practice and on educational consequences of this, as well on some paradoxes in education today. Among the main reasons for the difficulties are discussed: the interpretation of reflection, the disregard for the specifics of the profession of the FL teacher in curriculum standards and administrative regulations and the negative influence of market-oriented ideology on education and teacher training. The lack of comprehension of, and/or the misinterpretation of the idea of reflection have negative consequences for education and teacher training. The article concludes with some suggestions for the teacher and pupil education, including a broadly understood idea of reflection.